Distribution of Genetic Factors Associated with Severe COVID-19 in Ethnic Groups of the Eastern Caucasus - S. Р. Abdullaev; К. М.-В. Mammaev; N. Р. Denisenko; I. l. Temirbulatov; A. А. Kachanova; E. V. Mikhaylenko; А. V. Kryukov; Т. Т. Valiev; К. В. Mirzaev; S. N. Mammaev; D. А. Sychev (Антибиотики и Химиотерапия, 2023)
Background. Previously, genetic markers rs11385942 G>GA and rs657152 C>A of disease severity were identified for COVID-19. The study of the prevalence of clinically significant genetic markers may be useful for the development of region-specific approaches to disease control, considering, among other things, the ethnic composition of the territory, which is especially relevant for Russia. Based on the ethnic heterogeneity of the population of the Republic of Dagestan, this region was chosen as an example to study the distribution of COVID-19 severity markers of interest. Objective. Investigation of the prevalence of rs11385942 G>GA and rs657152 C>A markers among five ethnic groups residing in Dagestan. Methods. The study included 605 healthy volunteers (158 men and 447 women) from five different autochthonous ethnic groups living in the Republic of Dagestan: 118 Avars, 121 Dargins, 116 Laks, 127 Kumyks, and 123 Lezgins. Blood served as a material for determining polymorphisms. Carriage of polymorphic markers was determined by real-time polymerase chain reaction method. Results. The prevalence of rs11385942 G>GA marker ranges from 10.17% among Avars to 15.04% among Lezgins; significant differences were found in comparison with Russian ethnic group from literature sources. The second marker – rs657152 A>C — is distributed relatively homogeneously in the studied groups, without significant differences, and correlates with the data on the frequency of marker detection among Russians, as well as among European populations and worldwide — 50–60%. Conclusion. No differences were found within the ethnic groups of Dagestan in the carriage of both studied COVID-19 severity markers. At the same time, the rs11385942 G>GA marker detection frequency in the analyzed groups was on average higher in comparison with Russians and the average values for European populations.